Corrosion behaviour of WC-10% AISI 304 cemented carbides - Oliveira, A. B.
The corrosion behavior of tungsten carbide hard metal composites with AISI 304L stainless steel as binder matrix and a WC-Co composite with similar grain size and binder content was investigated using electrochemical techniques (open circuit potential monitoring, current-potential curves, electrochemical impedance spectroscopy, scanning vibrating electrode technique) and scanning electron microscopy. (C) 2015 Elsevier Ltd. All rights reserved.